(untitled) (Journal of Advances and Scholarly Researches in Allied Education, 2023)
A bank is a financial institution that receives deposits from the public and lends those funds to individuals, businesses, and governmental entities. The government owns a sizable stake in the banks that make up the "public sector." To be clear, private sector banks are those that do not have any ownership from the government. In India’s early banking history, the industry was controlled by public sector banks. The banking industry has been essential in averting economic downturns, as India commemorates its 65th anniversary and continues to expand at a phenomenal rate second only to China among the world’s fastest-growing economies. Since a strong banking system supports a nation’s steady industrial and economic progress, the banking sector’s success reflects the nation’s economic activity. The regulatory and governmental organisations can learn about the efficacy of current policies and the need for possible revisions by investigating the financial health of these banks